Answers

2015-06-08T19:41:15+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
So we have:
2(x+y)(7x-2y)
We perform the FOIL method on the terms in bold.
First: x * 7x = 7x²
Outer: x * -2y = -2xy
Inner: y * 7x = 7xy
Last: y * -2y = -2y²

So:
2(x+y)(7x-2y)
2(7x²-2xy+7xy-2y²)
= 2(7x²+5xy-2y²)
= 14x²+10xy-4y²


0